Significance of diffusion weighted imaging (DWI) as an improving factor in contrast enhanced magnetic resonance imaging (MRI) enterography in evaluation of patients with Crohn’s disease - Bilal Imširović; Enver Zerem; Alma Efendić; Alma Mekić Abazović; Omar Zerem; Muhamed Djedović (Medicinski glasnik, 2018)
Aim: To determine capabilities and potential of contrast enhanced magnetic resonance imaging (MRI) enterography in order to establish the diagnosis and to evaluate severity and activity of intestinal inflammation. Methods: Fifty-five patients with suspicion for presence of Crohn's disease were evaluated. All patients underwent contrast enhanced MRI enterography and diffusion weighted imaging (DWI), and subsequently endoscopic examination or surgical treatment. Four parameters were analysed: thickening of the bowel wall, and presence of abscess, fistula and lymphadenopathy. Results: Comparing results of DWI and contrast enhanced MRI enterography a significant difference between results given through diffusion and histopathological test was found, e.g. a significant difference between results obtained through diffusion and MRI enterography was found. MRI enterography sensitiveness for bowel wall thickening was 97.7% and specificity 70%, whilst DWI sensitivity for bowel wall thickening was 84% and specificity 100%. The diagnostics of abscess and fistula showed no significant difference between DWI and MRI, while in lymphadenopathy significant difference between contrast enhanced MRI enterography and DWI was found. Conclusion: Contrast enhanced MRI enterography in combination with DWI allows for excellent evaluation of disease activity, but also problems or complications following it. The examination can be repeated, controlled, and it can contribute to monitoring of patients with this disease.
Keywords: magnetic resonance imaging; diffusion; inflammatory bowel disease